A novel tick protein supports integrity of gut peritrophic matrix impacting existence of gut microbiome and Lyme disease pathogens. (21st October 2020) - Yang, Xiuli; Koči, Juraj; Smith, Alexis A.; Zhuang, Xuran; Sharma, Kavita; Dutta, Shraboni; Rana, Vipin S.; Kitsou, Chrysoula; Yas, Ozlem B.; Mongodin, Emmanuel F.; Pal, Utpal
Abstract: The peritrophic matrix (PM) is an acellular membrane that covers the gut epithelium in arthropods and physically separates it from the lumen. The structure is thought to play an important role in tick biology. The PM is also known to impact the persistence of tick‐borne pathogens like Borrelia burgdorferi, although limited information is available about its molecular constituents or their biological significance. Herein, we characterise a novel PM‐associated gut protein in Ixodes scapularis ticks, annotated as P eritrophic M embrane C hitin B inding P rotein (PM_CBP), for its role in the integrity and function of the matrix. The PM_CBP displays homology to the chitin deacetylase metalloenzyme, shows upregulation during tick feeding, and is localized at the luminal surface of the gut epithelium. The structural integrity of the PM was impaired both by the knock down of PM_CBP expression via RNA interference and by treatment with anti‐PM_CBP antibodies, as revealed by its electron microscopic appearance. Additionally, the duration of tick engorgement on mice and the passage of experimentally‐inoculated fluorescent dextran molecules across the PM are affected by the knock down of PM_CBP expression. The transfer of anti‐PM_CBP antibodies into the tick gut impacted the overall composition of the resident microbiome, and also influenced B. burgdorferi acquisition in ticks and its transmission to mice. Taken together, these data highlight the biological significance of the Ixodes PM and suggest that the targeting of its molecular constituents may contribute to the development of novel interventions against tick‐borne infections. Abstract : The peritrophic membrane (PM) in tick gut covers the epithelial cells (EC) and physically separates them from the lumen. This study identified a PM‐associated protein in Ixodes ticks, called Peritrophic Membrane Chitin Binding Protein (PM_CBP), for its role in the integrity and function of the membrane. The normal PM integrity (upper image) can be impaired by treatment with anti‐PM_CBP antibodies (bottom image), as revealed by its reduced thickness seen under an electron microscope, ultimately impacting existence of gut microbiome and Lyme disease pathogens.